Developmental referrals of pre‐school children in a diverse community in England: The importance of parental migration for referral rates. (13th April 2022) - Allport, Tom; Ambrose, Alissamaryam; Collin, Simon M.
Abstract: Background: Children born to migrant parents have higher rates of language difficulties, intellectual disability and autism. This study explores the relationship between migration, ethnicity and reasons for early years referrals to community paediatrics in a diverse multi‐cultural population in a city in south west England. Methods: Observational retrospective study from a community paediatric service serving a multi‐cultural urban population from June 2012 to February 2016. We tested associations of ethnicity and parental birth origin with reason for referral (developmental or non‐developmental) for children under 5 years old and estimated crude rate ratios for referrals using population census data. Results: Data were available for 514 children (52% white or mixed race, 16% Asian, 21% African diaspora, and 11.5% Somali); 53% had two UK‐born parents while 22% had two migrant (non‐UK‐born) parents. Referrals were for developmental reasons in 307 (60%) including 86 for possible autism. Parental birth origin and ethnicity were associated with reason for referral ( p < 0.001). Children from African diaspora, Asian or Somali backgrounds had more than twice the rate (rate ratio [RR] 2.37, 95% CI 1.88–2.99, p < 0.001) of developmental referrals compared with white or mixed‐race children. Children of Somali or African diaspora ethnicity were, respectively, six‐times (RR 5.99, 95% CI 3.24–10.8, p < 0.001) and four times (RR 4.23, 95% CI 2.44–7.29, p < 0.001) more likely to be referred for possible autism spectrum than their white or mixed‐race peers. Developmental referral as a proportion of all referrals was twice as high among children with one migrant parent (20.4%) and three times as high among children with two migrant parents (29.5%), compared with children whose parents were both UK‐born (10.7%). Conclusions: This study supports the importance of ethnicity and parental migration as factors in young children experiencing developmental difficulties, especially concerns about social communication or autism.